Morgan Memorial, Shawmut Avenue, ca. 1950 - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking north of the the corner of Castle Street and Shawmut Avenue. In the foreground is a billboard and behind that is Morgan Memorial and the Good Will Workshops. 10 3/4 x 13 3/4 overall 10 15/16 x 13 7/8 Photographs